The Assessment of Antimicrobial and Anti-Biofilm Activity of Essential Oils against Staphylococcus aureus Strains - Caglar Ersanli; Athina Tzora; Ioannis Skoufos; Konstantina Fotou; Eleni Maloupa; Katerina Grigoriadou; Chrysoula (Chrysa); Dimitrios I. Zeugolis (MDPI AG, 2023)
The increase in antimicrobial resistance and tolerance over the years has become a serious public health problem, leading to the inevitable development of alternative antimicrobial agents as substitutes for industrial pharmaceutical antibiotics targeting humans and animals under the concept of one health. Essential oils (EOs) extracted from aromatic and pharmaceutical plants incorporate several bioactive compounds (phytochemicals) that positively affect human and animal health. Herein, this work aimed to examine a standardized chemical composition and screen the antimicrobial and anti-biofilm activity of Thymus sibthorpii, Origanum vulgare, Salvia fruticosa, and Crithmum maritimum EOs against three different Staphylococcus aureus strains by gold-standard disc diffusion, broth microdilution, and microtiter plate biofilm assays. Therefore, the evaluation of the above-mentioned EOs were considered as substitutes for antibiotics to combat the ever-mounting antimicrobial resistance problem. The observed bacterial growth inhibition varied significantly depending on the type and concentration of the antimicrobials. Thymus sibthorpii was determined as the strongest antimicrobial, with 0.091 mg/mL minimum inhibitory concentration (MIC) and a 14-33 mm diameter inhibition zone at 5% (v/v) concentration. All tested EOs indicated almost 95% inhibition of biofilm formation at their half MIC, while gentamicin sulfate did not show sufficient anti-biofilm activity. None of the methicillin-resistant strains showed resistance to the EOs compared to methicillin-sensitive strains. Thymus sibthorpii and Origanum vulgare could be potential alternatives as antimicrobial agents to overcome the problem of microbial resistance. The tested EOs might be incorporated into antimicrobial products as safe and potent antimicrobial and anti-biofilm agents.